Molecular based prevalence of shigatoxigenic Escherichia coli in rectal swab of apparently healthy cattle in Mymensingh district, Bangladesh - Hassan, Jayedul; Nazir, K. H. M. Nazmul Hussain; Parvej, Md. Shafiullah; Kamal, Tazrin; Rahman, Md. Tanvir (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: Cattle are regarded as the principle reservoir of O157 and non-O157 shigatoxigenic Escherichia coli (STEC). Spreading of the STEC to human is primarily happens through contaminated meat, milk and their byproducts. The present study was aimed to explore the occurrence of STEC in the rectal swab of apparently healthy cattle. Materials and methods: A total of 60 E. coli isolates that were previously isolated from the rectal swab of cattle were used in this study. DNA were extracted from the isolates and screened by PCR to detect E. coli stx (stx1, stx2), ehxA and rfbO157 genes. Representative amplicons of the PCR products were sequenced. The prevalence of the STEC was determined based on the detection of STEC specific stx genes. The prevalence data were further analyzed by SPSS to elucidate any difference among different demographic groups of the study population. Results: Overall, 43.33% (n=26/60) of the isolates were found carrying stx genes. Based on the presence of stx and ehxA genes, 6 different types of STEC were identified, of which 20% (n=12/26) were carrying both stx1 and stx2 genes. None of the isolates was positive for rfbO157. The PCR amplicons were sequenced, and the nucleotide sequences were deposited in GenBank (accession: KM596779-KM596784). Conclusion: In this study, non-O157 STEC were found highly prevalent in the local cattle. This study suggests that the apparently healthy cattle may act as a potential source of STEC infection for humans. http://doi.org/10.5455/javar.2017.d213 XML PubReader